HOME LEARNING PATTERN FOR INDONESIAN ELEMENTARY STUDENTS DURING COVID-19 PANDEMIC - Nurul Hidayah; Fitri Nur Mahmudah (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
Changes in educational arrangements due to Covid-19 have led to new system adjustments for all elements, especially parents. This study aims to determine the learning patterns at home for elementary school students during the Covid-19 pandemic. This study employed qualitative research methods. The approach used was a case study that was performed in the researcher's home environment. Participants consisted of six people and six schools. The data collection technique used a focus group discussion (FGD) with discussion guidelines. The research procedure employed the Creswell model. Data analysis was conducted with the Atlas.ti software version 8. This study observed learning patterns at home during the Covid-19 pandemic, which was by having indicators comprising of convenience place, parental assistance, activity, effective learning, and anticipate problems.